Economic Development Planning Analysis Food Crops Subsectors And Horticulture Crops Subsectors East Kalimantan Province - Yudi Fahriza; Siti Amalia; Juliansyah Roy (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to analyze commodities in the food crop subsector and horticultural crop subsector which have the potential to be developed in order to support the economy in East Kalimantan Province. Analyzing food crop subsector commodities and horticultural crop subsectors that have competitiveness to be developed in order to support the economy in East Kalimantan Province. Analyzing the shift and role of commodities in the food crop subsector and horticultural crop subsector in the economy in East Kalimantan Province. Analyzing economic development planning strategies that can be carried out in order to develop potential and competitive commodities in the food crop subsector and horticultural crop subsector to support the economy in East Kalimantan Province.In this research, an analysis was carried out to determine potential economic sectors using the Klassen typology analysis tool, then an analysis was carried out to explain competitive sectors and shifts in economic structure using the Shift Share analysis tool, then a SWOT analysis was carried out.The results of this research are food crop subsector commodities and horticultural crop subsectors that have the potential to be developed in order to support the economy in East Kalimantan Province are lowland rice, shallots and large chilies. Commodities in the food crop subsector and horticultural crop subsector that have competitiveness to be developed in order to support the economy in East Kalimantan Province are lowland rice, corn, bananas, shallots and large chilies. The economic development planning strategy that can be carried out in order to develop potential and competitive sectors in the food crop sub-sector and horticultural crop sub-sector in order to support the economy in East Kalimantan Province is to implement short-term, medium-term and long-term plans.